Seasonal cycles of phytoplankton and net primary production from Biogeochemical Argo float data in the south-west Pacific Ocean. (September 2022) - Chiswell, Stephen M.; Gutiérrez-Rodríguez, Andrés; Gall, Mark; Safi, Karl; Strzepek, Robert; Décima, Moira R.; Nodder, Scott D.
Abstract: We present annual cycles of chlorophyll a, phytoplankton carbon, nitrate and oxygen for Subtropical (STW), Subantarctic (SAW), and Subantarctic Mode (SAMW) waters near Aotearoa New Zealand from data collected by two Biogeochemical (BGC) Argo floats. We develop two simple models of depth-integrated net primary production (NPP), tuned against 14 C-uptake measurements, to compare with Vertically-Generalised Production Model (VGPM) satellite-based estimates of NPP. One model is the simplest possible, and assumes production is proportional to light multiplied by chlorophyll a concentration. The second model modifies the light response profile to account for photoacclimation. In STW at 30–35°S, enhanced production is initiated in austral autumn when the mixed layer deepens to entrain nutrients into the photic zone. For about half the year, there is substantial production within a deep chlorophyll maximum that sits below the mixed layer. Consequently, depth-integrated NPP is only loosely related to surface biomass as imaged from satellite remote-sensing, and BGC Argo-based model estimates of depth-integrated NPP are about double VGPM estimates. In SAW at 45–55°S, production is initiated when vertical mixing decreases in austral spring. Production is largely within the mixed layer, and depth-integrated phytoplankton biomass and depth-integrated NPP follow surface phytoplankton biomass. Model estimates of depth-integrated NPP based on BGC Argo float profiles are comparable with VGPM estimates for the southern water masses. Highlights: Seasonal cycles of primary production off NZ are determined from BGC-Argo data and simple models. Subtropical water shows an autumn bloom initiated by deep winter mixing. Subsurface production accounts for over half the total production in summer subtropical water. Subantarctic water shows a spring bloom initiated when deep winter mixing ceases. Subsurface production accounts for little total production in subantarctic water.